The effect of prosthetic alignment on the stump temperature and ground reaction forces during gait in transfemoral amputees - Cárdenas, Andres M.; Uribe, Juliana; Font-Llagunes, Josep M.; Hernández, Alher M.; Plata, Jesús A. (Gait & posture, 2022)
Lower limb prosthetic alignment is a procedure mostly subjective. A prosthetic misaligned induces gait deviations and long-term joint diseases. The alignment effects for each lower limb and the stump stays uncertain. To identify the effect of the transfemoral alignment prosthesis on ground reaction forces and thermal images of the residual limb. The effect of misalignment and nominal alignment was evaluated in sixteen transfemoral amputees. The nominal alignment was considered as the optimal alignment for each subject. Misalignment included random variations in the anterior-posterior and medial-lateral translation of the prosthetic foot and the angle of flexion-extension, abduction-adduction, and internal-external rotation of the socket and prosthetic foot. The control group consisted of fifteen non-amputee individuals. The ground reaction force parameters and stump temperature were analyzed for each alignment condition. The statistical analysis included the one-way ANOVA, Kruskal-Wallis, and multiple comparison tests. The prosthesis did not produce statistically significant changes in the average temperature of residual limbs. However, the temperature distribution on the stump skin was different (P < 0.05). The transfemoral prosthesis misalignment produced an irregular heat diffusion on the anterior, posterior, and lateral sides of the stump contour compared to the nominal alignment (P < 0.05). The sound limb did not show differences between nominal alignments and misalignments for most ground reaction force parameters. For almost all GRF parameters, significant differences were observed for the prosthetic limb between misalignment and nominal alignment (P < 0.001). The symmetry indices of ground reaction force parameters of transfemoral amputees did not show any kind of significant improvements after aligning the prosthesis nominally. The stump's temperature distribution and the ground reaction force findings for the prosthetic limb provide a better understanding of the alignment procedure of the transfemoral prosthesis and improve the amputees' compliance to the prosthesis. •The thermal images can support the prosthetist during the alignment procedure.•A poor prosthetic alignment produces an irregular heat distribution on the stump.•The GRF of the prosthetic limb is a useful indicator for the alignment procedure.•The GRF of the sound limb is not helpful indicators to aid the alignment procedure.•Symmetry indices do not improve after properly aligning the prosthesis.